Mechanisms of multisensory integration and attention - Gama, Nuno (2017)
Spatial attention is an essential mechanism that helps us perceive our surroundings by bringing into consciousness environmental occurrences or objects that may be of importance. Studies of spatial attention have classically recorded behavioural responses to targets presented in a region of space where attention had previously been allocated to. Such investigations show a behavioural facilitation at the same location due to cueing, but less in known about the effects of shifts of attention when the cued location is not the location of interest. This thesis presents seven experiments aimed at investigating this by implementing and revising the attentional repulsion effect (ARE). The ARE is a perceptual localisation error when attention is diverted from the region of interest and it has been extensively studied in the visual domain, however, the rising number of ARE studies has created numerous research methodologies used to evoke the effect, which may have led to isolated reports. This thesis attempts to combine past methodologies with a new approach to quantify the effect, and will address some methodological differences evident in the literature, in order to optimise the stimulus paradigms and maximise the effect. The results show that a robust ARE can be elicited in the visual modality, but the same is not observed in the auditory modality. Furthermore, when using cues that are of different modality than the targets, the ARE is only observed in the visual target modality. Using visual cues and auditory targets will produce an attraction effect, in line with the ventriloquism theory. However, the implementation of interstimuli intervals up to 1.5 seconds would be enough to disrupt the ventriloquism illusion, but it did not alter the resulted attraction. Lastly, one question regarding the role of attention in sensory adaptation was addressed. I hypothesise that sensory adaptation could be further a contributor to the ARE given that most psychophysics paradigms of the ARE repeat the same stimuli thousands of times, uninterruptedly. The results are inconclusive mainly due to experimental design. All results are discussed in relation with theories of spatial and multimodal attention.